2003
DOI: 10.1164/rccm.200208-963oc
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Effects of Gestational Intermittent Hypoxia in the Developing Rat

Abstract: Intermittent hypoxia (IH), one of the hallmarks of obstructive sleep apnea, occurs more frequently during pregnancy. We hypothesized that IH may lead to persistent postnatal changes in respiratory responses to acute hypoxia and may also lead to adverse effects on spatial function learning as revealed by the Morris water maze. To examine this issue, time-pregnant Sprague-Dawley rats were exposed to IH and room air (IHRA; 21 and 10% O2 alternations every 90 seconds) or to normoxia (RARA) until delivery. Ventilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(74 citation statements)
references
References 66 publications
7
67
0
Order By: Relevance
“…Chronic intermittent hypoxia (CIH) is present in obstructive sleep apnea (OSA), sickle cell anemia and asthma. [1][2][3][4][5][6][7] These various paradigms of hypoxia often result in different consequences on growth and development. Hypoxia leads to many consequences but one that affects individual subjects early in life is growth and development causing growth deficits or cognitive and behavioral abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic intermittent hypoxia (CIH) is present in obstructive sleep apnea (OSA), sickle cell anemia and asthma. [1][2][3][4][5][6][7] These various paradigms of hypoxia often result in different consequences on growth and development. Hypoxia leads to many consequences but one that affects individual subjects early in life is growth and development causing growth deficits or cognitive and behavioral abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…In rats, the most striking effect of neonatal CIH (10 and 21% O 2 alternating at 90-s intervals, 12 h/day for 30 days beginning on the first postnatal day) is an increase in normoxic ventilation that persists into adulthood, and it may be permanent (84,85); similar effects on normoxic ventilation have been reported following prenatal CIH (40). The magnitude of these effects, and their persistence, decreases with age at onset of exposure and are most pronounced when CIH commences during the first 2 postnatal wk (83,84).…”
Section: Developmental Plasticity In Respiratory Control: Examplesmentioning
confidence: 63%
“…Direct comparison of responses to acute intermittent versus continuous hypoxic challenge in piglets showed that the intermittent pattern produced greater decline in respiratory indices (20). In addition, gestational intermittent hypoxia in rats resulted in a decrease of ventilatory responses to subsequent acute hypoxia on p5 (21). One might therefore expect that intermittent recurrent hypoxia in rats throughout the developmental age used in this study would further enhance the decline in ventilatory responses to subsequent acute hypoxia in later life.…”
Section: Discussionmentioning
confidence: 80%